Urgensi dan Strategi Penguatan Literasi Media dan Digital dalam Pembelajaran Agama Islam - Agus Sulistyo; Ismarti (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2021)
Learning media is important component in the learning Islamic Religion Education. In the learning process on digital era, the teacher teachers are expected to be able to use various forms of instructional media. Therefore, media literacy and digital literacy must be owned by the teacher. These literacy were about the ability to know the various forms of digital learning media and understand the way, usability, function and purpose of use in the learning process. These are to make learning process more effective and efficient in delivering learners to achieve the planned learning objectives. This paper aimed to: (1) describe the role of media that can be used in the learning process of Islamic religion education; (2) to highlight the challenges of Islamic education in digital era; (3) to highlight urgency media literacy and digital literacy for Islamic religion teachers; and (40 to recommend the strategies for strengthening media literacy and digital literacy in Islamic religion education learning process.